Transcriptional profile of glucose‐shocked and acid‐adapted strains of Streptococcus mutans. (2nd July 2015) - Baker, J.L.; Abranches, J.; Faustoferri, R.C.; Hubbard, C.J.; Lemos, J.A.; Courtney, M.A.; Quivey, R.
Summary: The aciduricity of Streptococcus mutans is an important virulence factor of the organism, required to both out‐compete commensal oral microorganisms and cause dental caries. In this study, we monitored transcriptional changes that occurred as a continuous culture of either an acid‐tolerant strain (UA159) or an acid‐sensitive strain ( fabM ::Erm) moved from steady‐state growth at neutral pH, experienced glucose‐shock and acidification of the culture, and transitioned to steady‐state growth at low pH. Hence, the timing of elements of the acid tolerance response (ATR) could be observed and categorized as acute vs. adaptive ATR mechanisms. Modulation of branched chain amino acid biosynthesis, DNA/protein repair mechanisms, reactive oxygen species metabolizers and phosphoenolpyruvate:phosphotransferase systems occurred in the initial acute phase, immediately following glucose‐shock, while upregulation of F1 F0 ‐ATPase did not occur until the adaptive phase, after steady‐state growth had been re‐established. In addition to the archetypal ATR pathways mentioned above, glucose‐shock led to differential expression of genes suggesting a re‐routing of resources away from the synthesis of fatty acids and proteins, and towards synthesis of purines, pyrimidines and amino acids. These adjustments were largely transient, as upon establishment of steady‐state growth at acidic pH, transcripts returned to basal expression levels. During growth at steady‐state pH 7, fabM ::Erm had a transcriptional profile analogous to that of UA159 during glucose‐shock, indicating that even during growth in rich media at neutral pH, the cells were stressed. These results, coupled with a recently established collection of deletion strains, provide a starting point for elucidation of the acid tolerance response in S. mutans .